(untitled) (Revue D’études Interculturelles De L’image, 2012)
Our fascination with the surveillance video of oil gushing from the British Petroleum Gulf Spill in 2010 expresses a paradox: our ultimate irrelevance to technological progress apparently undertaken for our benefit, in our name, and in response to our demand. These images present a visual model for all future disasters: here, something is happening but nothing is changing. This picture of disaster without progression and syntax has been witnessed before but only on stage, in Samuel Beckett’s Waiting for Godot and Endgame. Art has mustered only a weak rejoinder to the subdued shudder inspired by the BP video. Our fascination with the BP footage is echoed faintly in our response to Edward Burtynsky’s OIL. In his photographs of the petroleum industry, Burtynsky removes the human measuring stick, thereby triggering our sense of the enormity (both of the size and of the crime) of the petroleum industry. Yet unlike the BP video, these images recuperate our horror at the obscure scale of what they show us. Instead of recoiling from Burtynsky’s work, the viewer is placated through an appreciation for the artist’s control of his medium and its iconic language.